Patronizing the Mass: How Middle-Agents Deepened Populism and Post-Truth in Indonesia 2019 Presidential Election - Haq, Muhammad Naziful (Jurnal Politik, 2021)
Indonesian 2019 presidential election was extensively highlighted as a populist rematch between the technocratic Jokowi and the chauvinist Prabowo. There were at least two dimensions that contributed to the existing populist atmosphere at the presidential election: the religio-social condition of the people and the personal appearance of the presidential candidates. By referring to the two factors, analysts predominantly mentioned that Prabowo was more populist than Jokowi due to his energetic rhetoric and chauvinist discourse. However, it is undeniable that the polarization at the grassroots level was equally vitriolic in both Jokowi and Prabowo supporters. To what extent, then, could a person with a subtle populist gesture and rhetoric such as Jokowi could have vitriolic supporters and a deep post-truth condition. The research at hand underlines social media and middle-agents as additional tenets for the emerging entrenchment between the two supporters. Using content analysis, this research unpacks the populism and post-truth energy of a small sample of tweets and comments to comprehend how the interaction of the people and middle-agents could deepen populist cleavage and post-truth condition. This research found that, although Jokowi and Prabowo envisaged a different populist style at the front of the electoral stage, the articulation of divisive discourse, trolling, and mockery are equally sparkling from their middle-agents in social media.